Oxidative Stress Induces Neuronal Apoptosis Through Suppressing Transcription Factor EB Phosphorylation at Ser467 - Qian Su; Bin Zheng; Chen-yao Wang; Yun-zhi Yang; Wen-wen Luo; Shu-min Ma; Xin-hua Zhang; Dong Ma; Yan Sun; Zhan Yang; Jin-kun Wen; Zhi-xue Liu (Cellular Physiology and Biochemistry, 2018)
Background/Aims: This study determined the role and mechanism of action of transcription factor EB (TFEB) in H2O2-induced neuronal apoptosis. Methods: SH-SY5Y cells were treated with Akt inhibitor/activator and different concentrations of H2O2. Cell apoptosis was detected by flow cytometric analysis. Akt and TFEB phosphorylation and PARP cleavage were determined by Western blotting. HEK293T cells were transfected with different truncated TFEB mutants and HA-Akt-WT; SH-SY5Y cells were transfected with Flag-vector, Flag-TFEB, Flag-TFEB-S467A or Flag-TFEB-S467D; and TFEB interaction with Akt was determined by co-immunoprecipitation and GST pull-down assays. Results: A low concentration of H2O2 induces TFEB phosphorylation at Ser467 and nuclear translocation, facilitating neuronal survival, whereas a high concentration of H2O2 promotes SH-SY5Y cell apoptosis via suppressing TFEB Ser467 phosphorylation and nuclear translocation. The TFEB-S467D mutant is more easily translocated into the nucleus than the non-phosphorylated TFEB-S467A mutant. Further, Akt physically binds to TFEB via its C-terminal tail interaction with the HLH domain of TFEB and phosphorylates TFEB at Ser467. Mutation of TFEB-Ser467 can prevent the phosphorylation of TFEB by Akt, preventing inhibition of oxidative stress-induced apoptosis. Conclusions: Oxidative stress induces neuronal apoptosis through suppressing TFEB phosphorylation at Ser467 by Akt, providing a novel therapeutic strategy for neurodegenerative diseases.